2022
DOI: 10.1038/s12276-022-00853-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phospholipase D1 induces immunogenic cell death and potentiates cancer immunotherapy in colorectal cancer

Abstract: Phospholipase D (PLD) is a potential therapeutic target against cancer. However, the contribution of PLD inhibition to the antitumor response remains unknown. We developed a potent and selective PLD1 inhibitor based on computer-aided drug design. The inhibitor enhanced apoptosis in colorectal cancer (CRC) cells but not in normal colonic cells, and in vitro cardiotoxicity was not observed. The inhibitor downregulated the Wnt/β-catenin signaling pathway and reduced the migration, invasion, and self-renewal capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Urbahn et al found that TNF-a and IL-6 were reduced in the plasma of septic shock mice knocked out of the PLD1 gene, and mortality was also lesser (64). Hwang et al developed A3373, a potent inhibitor of PLD1, and this inhibitor was found to selectively bind to PLD1 to inhibit PLD1 activity (65). In our opinion, this inhibitor may also be effective in treating septic shock.…”
Section: The Role Of Cargos Loaded Into Engineered Evs In Inhibiting ...mentioning
confidence: 84%
“…Urbahn et al found that TNF-a and IL-6 were reduced in the plasma of septic shock mice knocked out of the PLD1 gene, and mortality was also lesser (64). Hwang et al developed A3373, a potent inhibitor of PLD1, and this inhibitor was found to selectively bind to PLD1 to inhibit PLD1 activity (65). In our opinion, this inhibitor may also be effective in treating septic shock.…”
Section: The Role Of Cargos Loaded Into Engineered Evs In Inhibiting ...mentioning
confidence: 84%
“…They also demonstrated that combining SR-4835 with anti-PD-1 can significantly inhibit tumor growth, providing a potential combination therapy for breast cancer ( Li et al, 2020 ). Hwang et al (2022) designed a phospholipase D (PLD) inhibitor to induce ICD to regulate TME in colorectal cancer, expecting to offer a promising strategy through this target drug. Moreover, researchers developed a novel fluorinated mitochondria-disrupting helical polypeptide to elicit mitochondrial dysfunction in murine colon adenocarcinoma CT26 cells.…”
Section: Icd Inducers and Molecular Mechanismmentioning
confidence: 99%
“…PLD1 has been identified as a cell mobility regulator. The absence of PLD1 in vitro models resulted in decreased blood–brain barrier and chemokine-induced lymphocyte static adherence to intercellular adhesion molecule 1 and vascular cell adhesion molecule 1, as well as reduced cell migration and motility [ 78 ]. The disease severity was reduced in experimental allergic encephalomyelitis (EAE) mice lacking PLD1 [ 79 ].…”
Section: Roles Of Pld In Neurodegenerative and Neuroimmune Diseasesmentioning
confidence: 99%